FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MALNUTRISI PADA LANSIA DI RAWAT INAP RSUP FATMAWATI PERIODE FEBRUARI-MARET 2020 - Juwita Cindi Astari (2020)
Elderly is one of the susceptible groups fromany disease because there has been a change in the function of body tissues and organs slowly. The problem that is often faced by the elderly is malnutrition. Malnutrition is an imbalance between the nutrients eaten and the needs needed. Factors that can affect malnutrition are food intake, disease history, age and knowledge. This study aims to determine the factors associated with the incidence of malnutrition in the elderly in the inpatient care of Fatmawati General Hospital on February-March 2020. The design of this study was a cross section with sample of 54 patients who met the inclusion criteria using total sampling techniques. Data were obtained from respondent questionnaire, 2x24 hour food recall questionnaire, nutrition knowledge questionnaire, medical record, and demographic data. The Chi-square studies had shown the factors associated with the incidence of malnutrition were the age variable (p value = 0.007; OR = 4,800 95% CI 1,498-15,380), gender (p value = 0.003; OR = 0.167 95% CI 0.050-0.551), history of disease (p value = 0.016; OR = 0.174 95% CI 0.042-0.717), energy intake (p value = 0.000; OR = 22.619 95% CI 5.158-99.187). The logistic regression test results had proved showed that the incidence of malnutrition in elderly patients at RSUP Fatmawati most affected by energy intake (odds ratio 16,671; 95% CI 2,649-104,897).